Electronics math - Deem, Bill R.; Deem, Bill. ([S.l.] : Prentice Hall College Div, 1996)
This best-seller gets readers involved - hands-on - in a thorough, complete, practical study of electronics math and its relationship to the world of electronics. The Fifth Edition more effectively suits the needs of users and has been updated and reviewed to ensure both currency and accuracy. There's a new chapter on statistics in an effort to provide technicians with all of the tools required on the job; a new section on conversions between decimals, fractions and percents; and new examples, practice problems and end-of-chapter problems where appropriate.